1994
DOI: 10.1002/nt.2620020411
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effect of the bloom‐forming Trichodesmium sp. (cyanophyta) to the copepod Acartia tonsa

Abstract: The toxicity of the marine cyanobacterium Trichodesmium sp. to the copepod Acartia tonsa was assessed in a series of experiments during a Trichodesmium bloom off the North Carolina coast in late October 1992. Healthy intact cells of Trichodesmium sp. were not toxic to A. tonsa and were ingested by A. tonsa when no other foods were available. However, homogenized Trichodesmium cells were toxic to A. tonsa, suggesting that Trichodesmium sp. contains certain type(s) of intracellular biotoxins. This hypothesis was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
2
44
0
1
Order By: Relevance
“…These results agree with previous studies that found the presence of substances toxic to invertebrates in extracts of T. erythaeum from the São Paulo coast (10). Guo and Tester (6) showed that while intact, cells…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results agree with previous studies that found the presence of substances toxic to invertebrates in extracts of T. erythaeum from the São Paulo coast (10). Guo and Tester (6) showed that while intact, cells…”
Section: Resultsmentioning
confidence: 99%
“…The role of toxic substances in Trichodesmium spp. is related mainly to allelopathic functions, which may be very important since these organisms live in environments with low nutrient availability, indicating that competition for this resource may be high (6). Therefore, allopathic substances could be of evolutionary importance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxicity tests conducted with Trichodesmium sp. cells on the copepod Acartia tonsa demonstrated that intact cells were not toxic to A. tonsa, but the homogenized cells were (Guo and Tester, 1994). Thus the authors suggested that the alga contained one or more intracellular biotoxins.…”
Section: Cyanobacterial Toxinsmentioning
confidence: 87%